Sensitivity and specificity of microRNA‐122 for liver disease in dogs. (2nd August 2018) - Oosthuyzen, W.; Ten Berg, P.W.L.; Francis, B.; Campbell, S.; Macklin, V.; Milne, E.; Gow, A. G.; Fisher, C.; Mellanby, R.J.; Dear, J.W.
Abstract : Background: Current tests for diagnosing liver disease in dogs are sub‐optimal. MicroRNA‐122 (miR‐122) is a sensitive and specific biomarker of liver injury in humans and rodents. Circulating miR‐122 could have utility in identifying dogs with liver disease. Objective: Establish the reference interval for miR‐122 in healthy dogs and determine performance in a range of dog breeds with liver disease and control animals with non‐liver disease. Animals: Stored serum from 120 healthy dogs, 100 dogs with non‐liver diseases, and 30 dogs with histologically confirmed liver disease was analyzed. Methods: Retrospective study. Medical records of dogs with liver disease, non‐liver disease and healthy dogs were reviewed. Serum miR‐122 concentrations were measured by PCR and compared with the characteristics of the dogs and their conventional clinical measurements. Results: In healthy dogs the 2.5th, 50th, and 97.5th quartiles of miR‐122 were 110 (90% CI 80‐114), 594 (505‐682), and 3312 (2925‐5144) copies/μL, respectively. There was no difference between healthy dogs and dogs with non‐liver disease (median ± IQR: healthy dogs 609 [327‐1014] copies/μL; non‐liver disease 607 [300‐1351] copies/μL). miR‐122 was higher in dogs with liver disease (11 332 [4418‐20 520] copies/μL, P < .001 compared to healthy dogs). miR‐122 identified dogs with liver disease with high accuracy (receiver operating characteristic area under curve for comparison with healthy dogs: 0.93 [95% CI 0.86‐0.99]). The upper limit of normal for healthy dogs (3312 copies/μL) had a sensitivity of 77% and specificity of 97% for identifying liver disease. Conclusion and Clinical Importance: Liver disease can be sensitively and specifically diagnosed in dogs by measurement of miR‐122.